Hak Waris Anak Adopsi Menurut Kompilasi Hukum Islam - Yudhi Praneto; Dhio Dhani Sineba; Ifransyah Okta Irawan; Andre Kurniawan; Rozeino Saputra (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Islamic law regarding the inheritance distribution for adopted children is an important legal knowledge for Muslim families. This includes determining who will be the heirs, the share of each heir, and identifying the estate and inheritance of the deceased. An adopted child can bequeath a portion of their adoptive parents' estate, but not more than three-quarters of their wealth, according to Islamic law. This writing uses normative legal research. The Constitution of Islamic Law does not recognize the position of an adopted child concerning the inheritance of the adoptive parents' assets because there is no blood relationship between the adopted child and the adoptive parents. In Islamic law, the religious court that establishes the adoption of a child does not sever the child's lineage connection with their biological parents. Adopted children are not considered biological children and do not have the same rights and responsibilities as biological children.